The Valley of Fear - Doyle, Arthur Conan; Adapted by Flynn, Adrian (New York Oxford University Press, 2004)
Contains a play script, a note on staging, information about the characters and author and activities.
Keywords: Holmes, Sherlock -- Private Investigators -- Criminal Investigation